The Relationship between Sleep Quality and Sexual Function in Married Women: The Mediating Role of Stress - Moghtaderi Esfahani , Shabnam; Nayeb Darban, Nasim; Ghasemi , Maryam; Ejlal Noubarian , Masoumeh; Alimardani , Soroush (Psychology of Woman Journal, 2024)
Objective: this study aimed to examine the relationship between sleep quality and sexual function mediated by stress among married women.Methods and Materials: The present study is applied and descriptive-correlational in nature. The statistical population consisted of married women in the city of Babol (age range: 25 to 45 years). Using purposive sampling, 318 participants were selected for the study. They were assessed using the Sleep Quality Questionnaire (1989), the Female Sexual Function Index (2000), and the Perceived Stress Scale (1983). Statistical analysis was conducted using simultaneous regression with SPSS version 23.Findings: The results showed that sleep quality is a significant predictor of sexual function. Additionally, the role of sleep quality in predicting perceived stress was significant. The findings indicated that perceived stress is a significant predictor of sexual function, and the relationship between sleep quality and sexual function is mediated by perceived stress (P